2020
DOI: 10.2298/ijgi2001031p
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting conference participation decision-making

Abstract: Business travel, as the sector with the fastest growth in the tourism industry globally, has received increased attention from both countries and cities, particularly from emerging destinations. In developing economies, business travel, including attending meetings, conferences, incentives and other business events, often plays a leading role in the growth of the wider travel and tourism sector. Therefore, tourism authorities and convention bureaus at the national and city levels have been struggling to attrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 20 publications
7
40
1
5
Order By: Relevance
“…Previous studies have shown that conference factors significantly influence the decision to participate in a conference (Oppermann and Chon, 1997;Zhang et al, 2007;Pavlukovi c and Cimbaljevi c, 2020;Malek et al, 2011). Conference factors were ranked as one of the most significant motivations of conference participation (Malek et al, 2011).…”
Section: H2 Safety Measures Against Covid-19 Influence the Decision T...mentioning
confidence: 99%
“…Previous studies have shown that conference factors significantly influence the decision to participate in a conference (Oppermann and Chon, 1997;Zhang et al, 2007;Pavlukovi c and Cimbaljevi c, 2020;Malek et al, 2011). Conference factors were ranked as one of the most significant motivations of conference participation (Malek et al, 2011).…”
Section: H2 Safety Measures Against Covid-19 Influence the Decision T...mentioning
confidence: 99%
“…In Serbia, there is little research about business tourism in general and specifically the attractiveness of destinations and success factors that influence the decision-making process of meeting planners. Several previous studies addressed the conference attendees' satisfaction in Serbia (Dragićević et al, 2010;Dragićević et al, 2011;Dunjić et al, 2012), business tourism destination competitiveness (Dragićević et al, 2012), factors affecting conference participation decision-making from the academics' perspective (Pavluković, Cimbaljević, 2020). Moreover, there is a lack of research on Zlatibor as a business tourism destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Business tourism is deemed an important and fast-growing sector in the global tourism market (United Nations World Tourism Organization [UNWTO] & European Travel Commission [ETC], 2015;World Travel & Tourism Council, 2017;Pavluković, Cimbaljević, 2020). It has been considered as one of the most desirable forms of tourism development at destinations worldwide, as the spending of organizers and participants on business events related services (e.g., meeting facilities, accommodation, catering, transportation) and on tourism activities (e.g., dining, shopping, leisure, tours) contributes to the economic growth of host destinations (Han, Hwang, 2017;Han et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Destinations around the world have recognised the numerous benefits of hosting meetings and other events (Han and Hwang, 2017). In particular, emerging destinations have made significant capital investments in developing the infrastructure necessary for the meetings industry (Presbury and Edwards, 2005;Pavluković and Cimbaljević, 2020). Consequently, competition between destinations has become vigorous (Beardsley et al, 2019;UNWTO and ETC, 2015).…”
Section: Sitcon 2020 Tourism and Sustainable Development -Challengesmentioning
confidence: 99%
“…The meetings industry is an important and fast-growing sector of the global tourism industry (World Travel and Tourism Council, 2017;Han et al, 2019;Pavluković and Cimbaljević, 2020). Sometimes referred to as the "MICE" sector or business tourism, it is traditionally composed of four components -association conventions and congresses, corporate meetings, incentives and exhibitions, although this has also been widened to include networking events and hybrid forms of corporate events (Bladen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%